FEATURES OF THE REPRESENTATION OF THE MYTHOLOGICAL CONCEPTOSPHERE THROUGH LANGUAGE UNITS - Kdirbaeva, Gulzira (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
This article is dedicated to a comprehensive study of the representation of mythological conceptual sphere units through linguistic means. The research aims to explore how linguistic units reflect mythological concepts in various cultures and to analyze their semantic and structural characteristics. The article examines the lexical, phraseological, and symbolic components of mythological concepts, highlighting their historical and cultural transformations. Additionally, it investigates the linguistic-cognitive and linguisticcultural aspects of mythological units, as well as their role in shaping social and cultural memory within the context of intercultural communication. Special attention is given to the transmission of mythological meanings in interlingual communication, translation difficulties, and cultural gaps. The article presents a comparative analysis of the universal and national features of mythological concepts, using examples from different languages. The findings of the study can be valuable for understanding the linguistic expression of mythological thinking, as well as for research in translation theory, cognitive linguistics, and ethnolinguistics. Moreover, the article reveals the significance of mythological archetypes, symbols, and mythologemes in constructing the linguistic worldview and their role in intercultural communication from a linguistic-cognitive perspective. The research results provide insights into the linguistic representation of mythological concepts at various levels of analysis. In particular, it examines the lexical-semantic fields of mythological units, their metaphorical and associative features, and the methods of adapting their meanings in translation according to cultural contexts. This study contributes to a deeper understanding of the interconnection between language and culture, as well as how mythological units are preserved in linguistic consciousness and influence modern linguistic processes.